If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g + -24 = 81 Reorder the terms: -24 + 7g = 81 Solving -24 + 7g = 81 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 7g = 81 + 24 Combine like terms: -24 + 24 = 0 0 + 7g = 81 + 24 7g = 81 + 24 Combine like terms: 81 + 24 = 105 7g = 105 Divide each side by '7'. g = 15 Simplifying g = 15
| 4+c-2(x-6)=8 | | 5-3x=-2x+2 | | 4y+4+y=8y-8+6 | | 0.90=13.50 | | m-25/5-5m-3/4=1 | | 12x-9y=178 | | 12x-6612= | | -1(3y+3)-(-2y-4)=-4 | | F+8=-20+-f | | sinydx+(xcosy-y)dy=0 | | 3(1+2A)= | | 1/4(8x-16)=6x-20 | | 4e^(1/2x)-1=10 | | 8f=-6+7f | | n/-6=4-[-2] | | 2m+3(m-8)+1=46 | | 8x-13=7+9x | | 3x-0.5=5.5-x | | 3x+46=8x+6 | | -3(b-4)=3b-6 | | -2(4s-4)-8=-2(8s+6)-3 | | 6(5x+1)-6=3(4x+3) | | p+-3=10 | | x^2+y^2=6.25 | | 3.5=m/0.5 | | 4e^1/2-1=10 | | t=2s+4.66 | | 6z+11=47 | | 7x+14=8x+9 | | -100=-4r | | 7x-23=4x-5 | | -(x-5)=8x-4/-4 |